Why? ebook Explaining the holocaust. - Hayes, Peter (2017)
Featured in the PBS documentary, "The US and the Holocaust" by Ken Burns, Lynn Novick and Sarah Botstein "Superbly written and researched, synthesizing the classics while digging deep into a vast repository of primary sources." —Josef Joffe, Wall Street Journal Why? explores one of the most tragic events in human history by addressing eight of the most commonly asked questions about the Holocaust: Why the Jews? Why the Germans? Why murder? Why this swift and sweeping? Why didn't more Jews fight back more often? Why did survival rates diverge? Why such limited help from outside? What legacies, what lessons? An internationally acclaimed scholar, Peter Hayes brings a wealth of research and experience to bear on conventional views of the Holocaust, dispelling many misconceptions and challenging some of the most prominent recent interpretations.